2011
DOI: 10.1002/jsfa.4347
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antimicrobial activity ofSatureja montanaL. extracts

Abstract: The findings indicate that the bioactive extracts of S. montana have strong potential for use as natural antimicrobials and antioxidants in the preservation of processed food.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
3
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 34 publications
8
69
3
1
Order By: Relevance
“…Additionally, camphor was determined as the major compound of S. visianii Silic (Bezic et al, 2009;Dunkic & Bezic, 2008;Vidic et al, 2009). It is possible to increase the number of these kinds of examples as the following: isomenthone for S. boliviana (Dambolena et al, 2009;Hatami et al, 2011;Senatore et al, 1998), thymoquinone (Grosso et al, 2009b;Mastelic & Jerkovic, 2003;Palavra et al, 2011;Taborsky et al, 2012), geraniol (Cavar et al, 2008;Mastelic & Jerkovic, 2003;Radonic & Milos, 2003b), and carvacrol methyl ether (Serrano et al, 2011;Skocibusic & Bezic, 2004) for S. montana.…”
Section: Volatiles (Terpenes)mentioning
confidence: 99%
“…Additionally, camphor was determined as the major compound of S. visianii Silic (Bezic et al, 2009;Dunkic & Bezic, 2008;Vidic et al, 2009). It is possible to increase the number of these kinds of examples as the following: isomenthone for S. boliviana (Dambolena et al, 2009;Hatami et al, 2011;Senatore et al, 1998), thymoquinone (Grosso et al, 2009b;Mastelic & Jerkovic, 2003;Palavra et al, 2011;Taborsky et al, 2012), geraniol (Cavar et al, 2008;Mastelic & Jerkovic, 2003;Radonic & Milos, 2003b), and carvacrol methyl ether (Serrano et al, 2011;Skocibusic & Bezic, 2004) for S. montana.…”
Section: Volatiles (Terpenes)mentioning
confidence: 99%
“…carvacrol or thymol. Various techniques were used: 2,2-diphenyl-1-picryl hydrazyl (DPPH) radical scavenging assay [63,69,70,71,72], β-carotene bleaching test [68,70,72], thiobarbituric acid reactive species (TBARS) assay [67,69,73], ferric ion reducing antioxidant power (FRAP) assay [72], oxygen radical absorbance capacity assay [74] and method measuring the formation of hydroperoxydienes from linoleic acid [67]. With help of electron spin resonance (ESR) spectroscopy Fujisawa et al [75] found that eugenol and eugenol-related synthetic compounds possessed radical scavenging activity comparable with the activity of conventional antioxidants.…”
Section: Mutagenicity Anti-mutagenicity and Dna-protective Effectsmentioning
confidence: 99%
“…Several researchers reported herbs as rich sources of compounds with antimicrobial activity (Serrano et al, 2011;Giner et al, 2012). For meat products microbial safety is essential and the use of antimicrobials from herbs to improve the quality of meat has been an important field of research during recent years (Zhang et al, 2010;Radha Krishnan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%